A CRITICAL APPROACH TO TÜRKIYE’S COMPETITIVENESS IN WHEAT FLOUR AND PASTA EXPORTS (Third Sector Social Economic Review, 2023)
In this paper, Türkiye’s competitiveness in wheat flour and pasta sectors is analysed upon the definition and scope of the international competitiveness concept. Therefore, first, some definitions of international competitiveness are included. In this respect, it is understood that international competitiveness is based on non-price elements as much as price.  In addition, this concept is related to making more profit from the exports made rather than exporting a lot. To avoid measurement difficulties, this concept has been reduced to price competition mostly. It is also overlooked that price competition is not always the same thing as cost competition. However, international competitiveness at the sectoral level is based on either price competition arising from cost competition or non-price elements. In this direction, the goal of the sectors is not to sell much, but to increase profitability.Türkiye ranks first in world wheat flour exports and fourth in pasta exports.  Measurements based on export volumes and market shares reveal Türkiye’s competitive advantages in these sectors. In this paper, however, it is concluded that Türkiye’s exports in wheat flour and pasta sectors are largely based on price competition which arises not from low costs, but from price-cuts. These sectors are focused on selling a lot instead of gaining a lot.
Keywords: International competitiveness; international competitive power; flour sector; pasta sector; price competition